A phase I pharmacokinetic study of belinostat in patients with advanced cancers and varying degrees of liver dysfunction. Issue 11 (4th September 2019) - Takebe, Naoko; Beumer, Jan H.; Kummar, Shivaani; Kiesel, Brian F.; Dowlati, Afshin; O'Sullivan Coyne, Geraldine; Piekarz, Richard; Rubinstein, Lawrence; Fogli, Laura K.; Vaishampayan, Ulka; Goel, Sanjay; O'Bryant, Cindy L.; et al.
Abstract : Aims: The histone deacetylase inhibitor belinostat has activity in various cancers. Because belinostat is metabolized by the liver, reduced hepatic clearance could lead to excessive drug accumulation and increased toxicity. Safety data in patients with liver dysfunction are needed for this drug to reach its full potential in the clinic. Methods: We performed a phase 1 trial to determine the safety, maximum tolerated dose (MTD) and pharmacokinetics of belinostat in patients with advanced cancer and varying degrees of liver dysfunction. Results: Seventy‐two patients were enrolled and divided into cohorts based on liver function. In patients with mild dysfunction, the MTD was the same as the recommended phase 2 dose (1000 mg/m 2 /day). Belinostat was well tolerated in patients with moderate and severe liver dysfunction, although the trial was closed before the MTD in these cohorts could be determined. The mean clearance of belinostat was 661 mL/min/m 2 in patients with normal liver function, compared to 542, 505 and 444 mL/min/m 2 in patients with mild, moderate and severe hepatic dysfunction. Although this trial was not designed to assess clinical activity, of the 47 patients evaluable for response, 13 patients (28%) experienced stable disease. Conclusion: While a statistically significant difference in clearance indicates increased belinostat exposure with worsening liver function, no relationship was observed between belinostat exposure and toxicity. An assessment of belinostat metabolites revealed significant differences in metabolic pathway capability in patients with differing levels of liver dysfunction. Further studies are needed to establish formal dosing guidelines in this patient population.